Preparation of porous graphene-like material from coconut shell charcoals for supercapacitors. Issue 1 (1st January 2020) - Fahmi, Fahmi; Dewayanti, Nur Anggita Ayu; Widiyastuti, Widiyastuti; Setyawan, Heru
Abstract: High-surface area carbon with porous structure can provide a large electrical-double layer as energy storage in supercapacitors. Herein, porous graphene-like materials with high-surface area were prepared from renewable coconut shell charcoal via KOH activation followed by oxidation in a harsh environment using a modified-Hummer method. Using the method, the surface area of the treated coconut shell charcoal increased significantly from about 189.97 m 2 /g to 642.45 m 2 /g with a pore diameter of approximately 5 nm. As expected, the increase in surface area increased the capacitance significantly, by up to 46-fold, from 3.22 to 148.20 F/g. These results demonstrated that the low cost renewable porous graphene-like material prepared from coconut shell charcoals is promising for use as electrode material for supercapacitor.